2017
DOI: 10.1007/s12039-017-1357-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism studies on thermal dissociation of tri-n-octylamine hydrochloride with FTIR, TG, DSC and quantum chemical methods

Abstract: The thermal dissociation of tri-n-octylamine hydrochloride (TOAHCl) was investigated using both the quantum chemical simulation and experimental methods. The pathway through which a mixture of trin-octylamine (TOA) and hydrogen chloride (HCl), rather than din -octylamine (DOA) and 1-chlorooctane, are produced has been determined through transition state (TS) search with Intrinsic Reaction Coordinate (IRC) calculations. Particularly, strong agreement between the experimental FTIR spectra and that of TOA demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Thus, N‐H stretching vibrations are sensitive markers of the chemical environment. Such vibrations are typically strongly infrared active and are assigned in the range between 2700 and 2300 cm −1 region, usually as the summation bands . Red shifts would be observed when electron cloud density moves to nitrogen atom, denoting the decrease in vibration force constant, that is, bond strength or bond energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, N‐H stretching vibrations are sensitive markers of the chemical environment. Such vibrations are typically strongly infrared active and are assigned in the range between 2700 and 2300 cm −1 region, usually as the summation bands . Red shifts would be observed when electron cloud density moves to nitrogen atom, denoting the decrease in vibration force constant, that is, bond strength or bond energy.…”
Section: Resultsmentioning
confidence: 99%
“…Coenen, Kosswig et al had made extensive studies on the regeneration of tertiary amines from straight‐chain to branched‐chain through thermal dissociation of its chloride. Also, we have made some basic study on the thermal dissociation of solid TOAHCl . In comparison with branched‐chain tertiary amine tris(2‐ethylhexyl)amine (TEHA), it is much difficult to regenerate straight‐chain tertiary amine TOA by dissociation of their chlorides, with considerable higher temperature (with starting temperature of 170°C vs 100°C) and much longer time (with half‐life of 47 and 2 minutes in certain conditions, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the lower was the pH, the better was the regeneration. Previous studies have shown that the presence of strong acid can easily dissociate the complex [39,40]. The acid effect reduced the conditional stability constant of the complex.…”
Section: Effect Of Phmentioning
confidence: 98%
“…Therefore, additives can be used to release metal ions and facilitate the in situ recovery of cobalt ethylenediamine [38]. Previous studies indicated that a strong acid such as hydrochloric acid can dissociate the complex [39,40] using hydrogen chloride as the additive. Also, the denitration effect of original and regenerated of cobalt ethylenediamine is compared.…”
Section: Introductionmentioning
confidence: 99%